The Effect of Passing Practice With Playing Patterns on Football Passing Accuracy - Andrian, Moch; Sudrazat, Adang; Fauzi, Rizal Ahmad (Universitas Hamzanwadi, 2024)
The problem found among SSB Bina Putra Pamekar students is that there are still many students who do not pass correctly when playing football. Therefore, the researcher offers passing training using play patterns in order to improve passing accuracy in SSB Bina Putra Pamekar students. This study aims to examine the results of passing training using play patterns on passing accuracy in SSB Bina Putra Pamekar students. The research method used in this study is pre-experiment with the research design “the one group pretest posttest design”, or the absence of a control group, and the sample selection technique used is purposive sampling. The test or instrument used to measure the ability of passing techniques is adapted from Suparjo's soccer passing test, using data analysis of normality test, homogeneity test, paired sample T-Test test, and R-Square regression test. The findings obtained by the researchers were that passing training with play patterns was able to improve the passing accuracy of each participant by 63.8%. The remaining 36% is influenced by external factors. Based on the passing accuracy normality test data conducted with Kolmogorov-Smirnov, the normality test results for the pre-test value were 0.471, while the post-test value was 0.698. It can be concluded that the data is normally distributed because the significance value obtained is> 0.05, so H0 is accepted.